Clinical Trials Design in Operative and Non Operative Invasive Procedures - Itani, Kamal M.F.; Reda, Domenic J.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
The aim of this text is to provide the framework for building a clinical trial as it pertains to operative and non operative invasive procedures, how to get it funded and how to conduct such a trial up to publication of results. The text provides all details of building a scientifically and ethically valid proposal, including how to build the infrastructure for a clinical trial and how to move it forward through various funding agencies. The text also presents various types of clinical trials, the use of implantable devices and FDA requirements, and adjuncts to clinical trials and interaction with industry. Clinical Trials Design in Invasive Operative and Non Operative Procedures will be of interest to all specialists of surgery, anesthesiologists, interventional radiologists, gastroenterologists, cardiologists, and pulmonologists.
The Research Question and the Hypothesis -- Primary and Secondary Endpoints -- Intervention and Control Groups -- Subject Selection -- Clinical Phases of Device and Drug Evaluation with Emphasis on Early Phase Trials -- Overview of Randomized Clinical Trial and the Parallel Group Design -- Non-Inferiority and Equivalence Trials -- Factorial Designs -- Cross-over Trials -- Cluster-Randomized Clinical Trials -- Adaptive Trial Designs -- Pragmatic Trials -- Point of Care Clinical Trials -- Basic Statistical Considerations -- Methods and Testing of Randomization -- Sample Size Calculation -- Principles of Analysis -- Advanced Statistical Methods -- Missing Data -- Interim Monitoring -- Ethical Considerations in Clinical Trials -- IRB and Review Process for Multisite Trials -- Trial Advertising -- Payment to Research Participants -- Conflict of Interest -- Quality Control in Procedural Studies -- Pilot Studies -- Surgeon Training and the Learning Curve -- Using a Placebo or Sham Procedure as a Control: Ethics and Practicalities -- Patient Recruitment and Retention in Procedural Trials -- Equipoise in Interventional Trials -- Setting up a Clinical Trial Research Office -- Regulatory Considerations: The Clinical Research Coordinator -- Data Collection Forms -- Data Security -- Remote Monitoring of Data Quality -- Investigators Meetings -- Site Visits -- Data Safety Monitoring Board: Composition and Role -- Endpoints Committee -- Regulatory Issues with Devices in Clinical Trials -- Trial Registration and Public Access to Data -- Mistakes in Clinical Trials -- Combined Drugs and Procedure Trials -- Genomics in Clinical Trials -- Biomarkers as Adjuncts to Clinical Trials -- Patient-centered Designs (and Outcomes) -- Economic Evaluations -- Telemedicine and Mobile Technology -- Budgeting for a Clinical Trial -- Funding a Clinical Trial -- Writing Your Grant for the Patient Centered Outcomes Research Institute (PCORI) -- Designing Clinical Trials for Quality and Impact: The Department of Veterans Affairs Approach to Developing a Cooperative Study -- Publication.
Keywords: Medicine; Anesthesiology; Interventional radiology; Cardiology; Surgery; Medicine & Public Health; General Surgery; Anesthesiology; Interventional radiology; Cardiology